2011
DOI: 10.1176/appi.neuropsych.23.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Playing American Professional Football on Long-Term Brain Function

Abstract: The authors recruited 100 active and former National Football League players, representing 27 teams and all positions. Players underwent a clinical history, brain SPECT imaging, qEEG, and multiple neuropsychological measures, including MicroCog. Relative to a healthy-comparison group, players showed global decreased perfusion, especially in the prefrontal, temporal, parietal, and occipital lobes, and cerebellar regions. Quantitative EEG findings were consistent, showing elevated slow waves in the frontal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 26 publications
1
71
1
Order By: Relevance
“…Although we chose to categorize players with symptom onset during their career as having "chronic postconcussive syndrome" to highlight the lack of delay between exposure and symptom onset, the progressive course of some of these patients suggests a possible underlying neurodegenerative process and raises the hypothesis that there may be an "early" and "delayed" neurodegenerative phenotype following repeated TBI. While prior studies have reported impairment in executive function, 8,9 we found that there was significant variability in this domain. Depression was commonly identified across all groups, consistent with prior reports.…”
Section: Discussioncontrasting
confidence: 72%
“…Although we chose to categorize players with symptom onset during their career as having "chronic postconcussive syndrome" to highlight the lack of delay between exposure and symptom onset, the progressive course of some of these patients suggests a possible underlying neurodegenerative process and raises the hypothesis that there may be an "early" and "delayed" neurodegenerative phenotype following repeated TBI. While prior studies have reported impairment in executive function, 8,9 we found that there was significant variability in this domain. Depression was commonly identified across all groups, consistent with prior reports.…”
Section: Discussioncontrasting
confidence: 72%
“…71 Another study in former professional football players found significant decreases in regional cerebral blood flow across the whole brain, especially in the prefrontal poles, temporal poles, occipital lobes, anterior/posterior cingulate gyrus, hippocampus, and cerebellum. 72 MCI screens administered to these same athletes demonstrated a significantly increased prevalence of MCI and dementia in these athletes, compared to aged-matched control patients. 72 De Beaumont and colleagues recently sought to investigate the effects of having sustained a sports concussion more than 30 years before testing on cognitive and motor functions.…”
Section: Chronic Behavioral Sequelae After Repetitive Mild Traumatic mentioning
confidence: 84%
“…72 MCI screens administered to these same athletes demonstrated a significantly increased prevalence of MCI and dementia in these athletes, compared to aged-matched control patients. 72 De Beaumont and colleagues recently sought to investigate the effects of having sustained a sports concussion more than 30 years before testing on cognitive and motor functions. 73 This study demonstrated that, relative to a group of former athletes with no previous history of sports concussion, former athletes who sustained their last sports concussion more than 30 years ago exhibit cognitive and motor system alterations, show significant reductions on neuropsychological as well as electrophysiological measures of episodic memory and frontal lobe functions selected for their known sensitivity to MCI and early-onset AD, and display significant motor execution slowness.…”
Section: Chronic Behavioral Sequelae After Repetitive Mild Traumatic mentioning
confidence: 84%
“…Abundant evidence, summarized in Thatcher (2010), has verified the reliability of QEEG evaluation, and hundreds of scientific studies have been published using QEEG evaluations. These studies have found the QEEG to have documented ability to aid in the evaluation of conditions such as mild traumatic brain injury (TBI; and sports-related concussions), ADD=ADHD, learning disabilities, depression, obsessive-compulsive disorder, anxiety, panic disorder, drug abuse, autism, and a variety of other conditions (including schizophrenia, stroke, epilepsy, and dementia; e.g., Alper, Prichep, Kowalik, Rosenthal, & John, 1998;Amen et al, 2011;Barry, Clarke, Johnstone, McCarthy, & Selikowitz, 2009;Clarke, Barry, McCarthy, & Selikowitz, 2001;Clarke et al, 2007;Harris et al, 2001;Hoffman et al, 1999;Newton et al, 2004;Thatcher, 2010;Thatcher et al, 1999). QEEG has even been able to predict treatment outcomes from interventions with conditions such as ADD=ADHD (Suffin & Emory, 1995), and alcoholism and drug abuse (Bauer, 1993(Bauer, , 2001Prichep, Alper, Kowalik, John, et al, 1996;Winterer et al, 1998).…”
Section: Assessment Prior To Neurofeedback Trainingmentioning
confidence: 99%
“…Concussions and head injuries that cause emotional, cognitive, and behavioral problems occur as a result of many things such as motor vehicle accidents, war (Trudeau et al, 1998), and sports (McCrea, Prichep, Powell, Chabor, & Barr, 2010;McKee et al, 2009), including football (Amen et al, 2011), doing headers in soccer (Tysvaer, Stroll, & Bachen, 1989), and boxing (Ross, Cole, Thompson, & Kim, 1983).…”
Section: Tbi and Strokementioning
confidence: 99%